ANALISIS KONSEP DHARIBAH ATAS PAJAK MINIMUM GLOBAL OECD TERHADAP KEADILAN EKONOMI MULTINASIONAL - Shofa Robbani; Sri Wahyuni; fitrianti wahib; Muhammad Syukron Ni’am; Muhamad Zaini Yahya (IAIN BONE, 2026)
This study aims to analyze the concept of dharibah in Islamic economic perspective toward the global minimum tax policy initiated by the Organisation for Economic Co-operation and Development and the Group of Twenty, as well as its implications for the economic justice of multinational enterprises. This research is motivated by the increasing practices of global tax avoidance through base erosion and profit shifting (BEPS), which have led to unequal tax burden distribution among countries. The study employs a qualitative approach with normative analysis, examining international tax law frameworks alongside Islamic economic principles. The findings reveal that the global minimum tax aligns partially with the principles of dharibah, particularly in promoting public welfare (maslahah) and fostering global fiscal fairness. However, several inconsistencies remain, including unequal benefit distribution for developing countries, the uniform tax rate application, and the limited incorporation of ethical dimensions within the policy. From the perspective of dharibah, justice is not merely defined by equal tax rates, but also by proportional burden-sharing and alignment with public interest. Therefore, a more inclusive reconstruction of global tax policy is necessary by integrating substantive justice values within Islamic economics to achieve a fair and sustainable taxation system.